Review of Japanese Journal of Evaluation Studies (Volume 6, Number 1)--Special Topic: "Evidence-Based Evaluation" - Ryoh Sasaki (The Evaluation Center at Western Michigan University, 2006)
The Japan Evaluation Society (JES) was established in 2000. Since then, JES has published its professional journal twice per year (see the archives at http://www.idcj.or.jp/jes). The most recent issue-Volume 6, Number 1-was published in March 2006. It includes 12 papers and the summary report of the 6thannual conference held at Hiroshima University. With more than 200 pages, this issue marks the largest volume since the journal started. We can say that evaluation is becoming popular and receiving significant attention by academia and practitioners in Japan.